The Effect of Pineapple Leaf Compost Dosage on Soil Chemical Properties, Growth, and Yield of Soybean in Acid Dryland - Maria Lusia; Erni Hawayanti; Rizky Kurniawan Saputra (Universitas Muhammadiyah Palembang, 2026)
Acydic dryland is a type of marginal land characterized by low soil fertility, low organic matter content, and high soil acidity, which can constrain soybean growth and yield. The utilization of pinneapple leaf compost as a locally available organic matter source to improve acydic dryland conditions and support soybean growth and yield at different application rates, as well as to identify the rate providing the most favorable agronomic response, has received limited attention. This study aimed to analyze the effects of pinneapple leaf compost application rates on soil pH, soybean (Glycine max L.) growth, and yield in acidic dryland. A field experiment was conducted using a non-factorial Completely Randomized Design (CRD) consisting of six treatments: N1 = 1 t ha⁻¹, N2 = 2 t ha⁻¹, N3 = 3 t ha⁻¹, N4 = 4 t ha⁻¹, N5 = 5 t ha⁻¹, and N6 = 6 t ha⁻¹ of pinneapple leaf compost, with each treatment replicated four times, resulting in 24 experimental units. The parameters observed included soil pH, plant height (cm), number of productive branches (branches), root volume (mL), pod weight per plant (g), pod weight per plot (kg), and 100-seed weight (g). The results showed statistically,that pinneapple leaf compost application did not significantly affect soil pH, soybean growth, or yield in acydic dryland. However, descriptively, the highest values for all observed variables were obtained with the application of 5 t ha⁻¹ (N5). Although the treatment was not statistically different from the other treatments, the 5 t ha⁻¹ rate consistently produced the highest values for soil pH, plant height, number of productive branches, root volume, pod weight per plant, pod weight per plot, and 100-seed weight. The highest yield was indicated by a pod weight of 1.89 kg plot⁻¹, equivalent to 9.45 t ha⁻¹.